Avoidant Coping Mediates the Relationship between Self-Efficacy for HIV Disclosure and Depression Symptoms among Men who have Sex with Men Newly Diagnosed with HIV - Cherenack, Emily M. (AIDS Behav, 2018)
HIV diagnosis presents a critical opportunity to reduce secondary transmission, improve engagement in care, and enhance overall well-being. To develop relevant interventions, research is needed on the psychosocial experiences of newly diagnosed individuals. This study examined avoidant coping, self-efficacy for HIV disclosure decisions, and depression among 92 newly diagnosed men who have sex with men (MSM) who reported recent sexual risk behavior. It was hypothesized that avoidant coping would mediate the relationship between self-efficacy and depression. Cross-sectional surveys were collected from participants three months after HIV diagnosis. To test for mediation, multiple linear regressions were conducted while controlling for HIV disclosure to sexual partners. Self-efficacy for HIV disclosure decisions showed a negative linear relationship to depression symptoms, and 99% of this relationship was mediated by avoidant coping. The index of mediation of self-efficacy on depression indicated a small-to-medium effect. Higher self-efficacy was related to less avoidant coping, and less avoidant coping was related to decreased depression symptoms, all else held constant. These findings highlight the role of avoidant coping in explaining the relationship between self-efficacy for HIV disclosure decisions and depression.